Elit Korporatisme Industri Garam di Nusa Tenggara Timur - Ratumakin, Paulus Adrianus K.L; Sius, Karolus Tatu (Journal of Education on Social Science (JESS), 2023)
This research aims to reveal and explain the pattern of relations between the state (government elite) and the community, both the interest group (association elite) or the wider community (association members) in the salt industry in NTT. As a system of government, corporatism is still practiced, although with a model that is not as idealized by its early thinkers. Corporatism in practice has the opportunity to give birth to new elites as found in the research of the salt industry in NTT. The interests of the elites do not necessarily represent the interests of association members in general. Even in the salt industry, the interests of the elites conflict with the interests of members and the community. Government elites and business associations that have large resources of power manipulate customary institutions, churches, academics and communities to achieve their interests. This system also gives the state (government elite) authority and dominance over various decisions on the utilization of public goods (location of the salt industry or customary land) and determines which entrepreneurs invest (state dominance). Finally, the state is not present as a neutral referee for the contestation of various interests of citizens or associations of interest groups.